1995
DOI: 10.1172/jci118330
|View full text |Cite
|
Sign up to set email alerts
|

Clusterin promotes the aggregation and adhesion of renal porcine epithelial cells.

Abstract: The function of clusterin, a heterodimeric glycoprotein markedly induced in renal and other organ injuries, is un-clear. Since renal injury is accompanied by alterations in cell attachment, it is possible that clusterin functions to promote cell-cell and cell-substratum interactions. In this study, a single cell suspension of renal epithelial (LLC-PK1) cells was treated with purified human clusterin, resulting in timeand dose-dependent cell aggregation. Electron microscopy of the cell aggregates demonstrated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 47 publications
1
43
1
1
Order By: Relevance
“…By analyzing the expression levels of other recently identified CLU protein forms, to our surprise, we found that the Cl-I and Cl-II oligonucleotides did not exert any significant effect on the putative 55 kDa (n-CLU 55 ) CLU protein form in both KH OS and U-2 OS cells; only a minor effect on the 49 kDa c-CLU 49 protein form level was detected (Fig. 6, A and B), although the binding sites of the Cl-I or the Cl-II oligonucleotides are common between the s-CLU and n-CLU mRNAs (5).…”
Section: Os Cells As a Model System To Study Clu Function In Humanmentioning
confidence: 78%
See 1 more Smart Citation
“…By analyzing the expression levels of other recently identified CLU protein forms, to our surprise, we found that the Cl-I and Cl-II oligonucleotides did not exert any significant effect on the putative 55 kDa (n-CLU 55 ) CLU protein form in both KH OS and U-2 OS cells; only a minor effect on the 49 kDa c-CLU 49 protein form level was detected (Fig. 6, A and B), although the binding sites of the Cl-I or the Cl-II oligonucleotides are common between the s-CLU and n-CLU mRNAs (5).…”
Section: Os Cells As a Model System To Study Clu Function In Humanmentioning
confidence: 78%
“…Maturation of the primary translation molecule include disulfide bonding, conversion to a high-mannose endoplasmic reticulum-associated form of ϳ60 kDa, extensive additional N-linked glycozylation, and finally, proteolytic cleavage in the trans-Golgi compartments that result in the mature secreted heterodimeric CLU protein form of ϳ70 -80 kDa (3). Interestingly, another CLU protein form of ϳ55 kDa, designated as nuclear (n)-CLU 55 (4), has been recently described in MCF-7 cells. According to a recent study (5), this protein form originates, after apoptosis induction, from a 49-kDa primary product (c-CLU 49 ) that is translated from an alternatively spliced CLU transcript.…”
Section: Introductionmentioning
confidence: 99%
“…The biological activities of extracellular sCLU have been studied extensively; it was initially found to induce cell aggregation [39][40][41], and in the plasma it inhibited the cytolysis of complement membrane attack complex (MAC) by binding to the complement components [42][43][44], and was associated with both high-density lipoprotein (HDL) and low-density lipoprotein (LDL) complexes [33,45,46]. These studies suggest that sCLU in the blood may serve not only as an inhibitor of the lytic terminal complement cascade, but also as a regulator of lipid transport and local lipid redistribution.…”
Section: Biochemistry and Functions Of Sclumentioning
confidence: 99%
“…The human homolog of clusterin has also been given other names, including complement-lysis inhibitor (CLI), secreted protein 40 (SP-40), and apolipoprotein J (ApoJ). Clusterin participates in many biological processes such as cell adhesion, lipid transportation, complement inhibition, membrane recycling and apoptosis [15,30,31,34,36,41]. High levels of clusterin expression have been found to be positively correlated with severe pathophysiological states and conditions such as renal disease, neurodegenerative disease, atherosclerosis, myocardial infarction and cancer [6,10,27,37,40].…”
Section: Introductionmentioning
confidence: 99%